THE IMPLEMENTATION OF THE TWO STAY TWO STRAY LEARNING MODEL ASSISTED BY MIND MAPPING TO IMPROVE STUDENTS' UNDERSTANDING CONCEPT - Putri Dhia Amira Hasna; Mochammad Ahied; Nur Qomaria; Dw iBagus Rendy Astid Putera; Maria Chandra Sutarj (Jurnal Pembelajaran Sains, 2022)
This study aims to determine the implementation of the Two Stay Two Stray assisted by Mind Mapping to improve students' understanding of concept. The method used in this research is quasi-experimental in the form of a one-group pretest-posttest design. The research was conducted at SMP Islam Nurus Syamsi with a sample selection technique using the saturated sample method, namely class VIII students. Collecting data using observation, questionnaire, test, and documentation techniques. The data analysis technique used paired t-test. The results showed that: (1) the implementation of the two stay two stray  learning model with the aid of mind mapping got an average result of 97.15% with very good criteria, (2) there were differences in students' understanding of concepts before and after the application of the two stay two stray learning model assisted by mind mapping with a significance value of 0.000 < 0.05 H0 was rejected, (3) increase in students' understanding concept after the implementation of the two stay two stray learning model assisted by mind mapping in the medium category was 69,23% and the high category was 30,77% with an average gain value of 0.6531 included the medium category, (4) student responses to the implementation of the two stay two stray learning model assisted by mind mapping obtained an average percentage of 87.02% including the very good category.